2015
DOI: 10.1177/0958928715588704
|View full text |Cite
|
Sign up to set email alerts
|

Not all that glitters is gold: Long-term care reforms in the last two decades in Europe

Abstract: This article explores changes that took place in long-term care (LTC) policies during the last two decades\ud in six European welfare states. In this regard, it addresses three issues: (1) why reforms took place, (2) the\ud main actors and coalitions driving this process and the institutional mechanisms at work and (3) the main\ud outcomes of reform processes. In order to analyse the development of LTC policies, the article applies\ud theoretical concepts of historical institutionalism. Our interpretation is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 46 publications
0
86
0
4
Order By: Relevance
“…In their wide-ranging analysis of changes in long-term care (LTC) in six European countries in recent years, Ranci and Pavolini (2015) found that countries with less developed LTC systems have expanded their coverage and generosity -in other words, universalised -while countries with universalistic LTC models have moved in the opposite direction, towards what they call 'restricted universalism'. Our systematic assessment of the trajectory of change in Nordic eldercare deepens their analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In their wide-ranging analysis of changes in long-term care (LTC) in six European countries in recent years, Ranci and Pavolini (2015) found that countries with less developed LTC systems have expanded their coverage and generosity -in other words, universalised -while countries with universalistic LTC models have moved in the opposite direction, towards what they call 'restricted universalism'. Our systematic assessment of the trajectory of change in Nordic eldercare deepens their analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Germany and Japan provide examples of the universalisation of public support in a former residual system. In Germany, the focus is on public support of family care by cash payments, and in Japan (similar to Sweden), the focus is on the provision of publicly financed care services (Ranci & Pavolini, ; Saito, ; see the conceptual part of this article for the institutional dimensions of long‐term care systems).…”
mentioning
confidence: 99%
“…The "New Public Management" approach has been criticized with the arguments that private sector methods, such as the aim to increase produc-tivity, can have a negative impact on working conditions and service quality, while Brennan and collaborators (2012) stress a threat for class based segregation due to limited access to private services. Ranci and Pavolini (2015) point out that application of this method in Sweden led to standardization of tasks and to a larger number of service users per care worker.…”
Section: Mixed Economy Of Welfare and Marketization Of Social Servicementioning
confidence: 99%
“…Yet, in many European countries, long-term care needs of citizens are only partly met through public services, while care responsibility also lays with users and their families. Because of this, many countries from Continental, South and Central-Eastern Europe are putting back the focus on provision of family care within their long-term care policies (Ranci, Pavolini, 2015). A comparative study (Rostgaard, 2002) found that most of the European countries researched, understood the invaluable contribution of carers to society, to the processes of decreasing the dependency on residential care (without informal care many care recipients would face institutionalization), as well as the need to ease the burden of care work, especially through provision of respite care services as they enable informal carers to take a break from caring responsibilities, but also continue their work while receiving recognition for it.…”
Section: Support To the Informal Family Care Through Social Servicesmentioning
confidence: 99%